Step
*
1
1
1
of Lemma
sub-bag-map-equal
1. T : Type
2. U : Type
3. b2 : T List
4. f : T ⟶ U
5. c1 : U List
6. cs : T List
7. map(f;b2) = (map(f;b2) @ map(f;cs) @ c1) ∈ bag(U)
8. {} = (map(f;cs) + c1) ∈ bag(U)
9. (map(f;cs) + c1) = {} ∈ bag(U) supposing (map(f;cs) = {} ∈ bag(U)) ∧ (c1 = {} ∈ bag(U))
10. map(f;cs) = {} ∈ bag(U)
11. c1 = {} ∈ bag(U)
⊢ cs = {} ∈ bag(T)
BY
{ ((RW assert_pushupC (-2) THENA Auto)
   THEN Unfold `bag-null` (-2)
   THEN Fold `bag-map` (-2)
   THEN (RWO "bag-map-null" (-2) THENA Auto)
   THEN Fold `bag-null` (-2)
   THEN RW assert_pushdownC (-2)
   THEN Auto) }
Latex:
Latex:
1.  T  :  Type
2.  U  :  Type
3.  b2  :  T  List
4.  f  :  T  {}\mrightarrow{}  U
5.  c1  :  U  List
6.  cs  :  T  List
7.  map(f;b2)  =  (map(f;b2)  @  map(f;cs)  @  c1)
8.  \{\}  =  (map(f;cs)  +  c1)
9.  (map(f;cs)  +  c1)  =  \{\}  supposing  (map(f;cs)  =  \{\})  \mwedge{}  (c1  =  \{\})
10.  map(f;cs)  =  \{\}
11.  c1  =  \{\}
\mvdash{}  cs  =  \{\}
By
Latex:
((RW  assert\_pushupC  (-2)  THENA  Auto)
  THEN  Unfold  `bag-null`  (-2)
  THEN  Fold  `bag-map`  (-2)
  THEN  (RWO  "bag-map-null"  (-2)  THENA  Auto)
  THEN  Fold  `bag-null`  (-2)
  THEN  RW  assert\_pushdownC  (-2)
  THEN  Auto)
Home
Index